Affect-regulated exercise: an alternative approach for lifestyle modification in overweight/obese women with polycystic ovary syndrome. (2nd December 2015) - Costa, Eduardo Caldas; de Sá, Joceline Cássia Ferezini; Costa, Ingrid Bezerra Barbosa; Meireles, Rodrigo da Silva Rosa Veleda; Lemos, Telma Maria Araújo Moura; Elsangedy, Hassan Mohamed; Krinski, Kleverton; Azevedo, George Dantas
Abstract: Objective : Affect-regulated exercise ("ARE") is an alternative approach to guide exercise intensity based on feeling of pleasure. The aim of this study was to analyze if overweight/obese women with polycystic ovary syndrome (PCOS) meet the American College of Sports Medicine (ACSM) recommendation regarding to exercise intensity to improve health status during a single bout of "ARE". Methods : A sample of 14 overweight/obese women with PCOS (18–34 years) performed a single bout of "ARE" (40 min of aerobic exercise on outdoor track). The Feeling Scale (FS) was used to guide "ARE" intensity/pace maintaining an affective valence between "good" and "very good" during all time. Heart rate (HR), speed, % of HR at first and second ventilatory threshold (VT1 and VT2 ) and time spent at moderate (64–76% of HRmax ) and vigorous (77–95% of HRmax ) intensity during "ARE" were measured with a global positioning system (GPS) device. Results : Volunteers exercised at 73% (68–78%) of HRmax, 5.8 (5.2–6.2) km/h, 93.4% of HR at VT1 (89.3–98.2) and 80.5% of HR at VT2 (75.3–84.6) and spent >80% of time at moderate intensity. Conclusions : Overweight/obese women with PCOS met the ACSM recommendation regarding exercise intensity to improve health status when exercised between "good" and "very good" of FS. Thus, "ARE" may be an interesting approach to be used in clinical practice regarding to exercise prescription and/or physical activity advice.